Pemberdayaan UMKM “Dhe Irma” Guna Meningkatkan Efisiensi Produksi dan Aspek Keuangan melalui Pengabdian Masyarakat: Empowerment of Dhe Irma's MSMEs to Increase Production Efficiency and Financial Management through Community Service - Nirwana, Nihlatul Qudus Sukma; Wulandari, Indah Apriliana Sari; Hermawan, Sigit; Arista, Sintha Wahyu; Sari, Nilam (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Productive MSMEs can have great potential to progress, mainly if they are well managed. This Community Service (Abdimas) program aims to empower the Dhe Irma MSME to increase production efficiency and financial management. Achieving Sustainable Development Goals (SDGs) No. 8, or